Morphology and molecular identification of Candida Species isolated from oral pediatric - Ream Samy; Diyaa Aljaza (مجلة علوم ذي قار, 2023)
In newborns, Candida is responsible for the common oral thrush and rash in skin folds and in the diaper area. Before the advent of modern sanitary measures and topical antifungal treatments, infants died from dehydration due to severe oral mucocandidiasis. Oral thrush is more likely to occur in infants and older adults due to reduced immunity. The study aimed to shed light on the relationship between Thrush and Candidia and To molecular identification of Candidia spp. isolated from Thrush. There are 100 samples of Oral swabs collected from pediatric with Thrush at ages ranging from (1day-12 years). All samples cultured on SDA, MSA and MEA. Several tests were used to identify the types of isolated yeasts, including growth on Chromogenic agar medium, as well as biochemical and molecular tests using primers ITS1, ITS4. The Results found that a six species of Candida were isolated on Chromogenic: C. albicans, C. glabrata, C. tropicalis, C. dubliniensis, C. krusei and C. kefyr, Also, showed the number of yeasts that were genetically diagnosed by molecular diagnosis was five species of yeasts as follows 2 isolates C. tropicalis from 22% and one isolate for each of the following types C. albicans, C. kefyr, C. dubliniensis and C. spp with 11% of all isolates where C. albicans showed the highest percentage. The results of the statistical analysis of the isolates showed that the most affected age group of pediatric was (month-1 year) in the rate of 24%. Antifungal susceptibility was studied, as the results indicated that all Candida isolates were sensitive to itraconazole,  while all Candida isolates were resistant to fluconazole Furthermore, most types of Candida were resistant to Nystatin and Amphotericin B, except for three type’s C. krusei, C. glabrata, and C. kefyr. The most common pathogen in pediatric is Candida spp. In pediatric, the results indicated that the best treatment to eliminate Candida Itraconazol, Clotrimazol, Nystatin, and Amphotricine B  Nystatin respectively